beta-Endorphin and adrenocorticotrophin after incremental exercise and marathon running--female responses - Heitkamp, H. C.; Huber, W.; Scheib, K. (European Journal of Applied Physiology, 1996)
Investigations of exercise-induced increases in beta-endorphin, adrenocorticotropic hormone (ACTH) and cortisol concentration have been carried out mainly in men. Data concerning the female reaction are sparse and less clear. In a comparison between incremental exercise and marathon running 14 experienced female marathon runners volunteered to run to exhaustion according to an incremental treadmill protocol. They ran a marathon 4 weeks later. Blood was analysed for beta-endorphin, ACTH and cortisol concentration immediately prior to the laboratory treadmill test, 3, 30 and 60 min later, as well as prior to the marathon, after 60 min and 120 min of running and 3, 30 min, and 24 h after completion of the run. At each blood collection, lactate concentration, heart frequency and perceived exertion were determined. The mean marathon running time was 3.22 h. Baseline concentrations for beta-endorphin of 22 pmol.l-1 before the marathon and 19 pmol.l-1 before the treadmill exercise increased 1.4-fold 30 min after the marathon and 1.9-fold after the treadmill exercise; for ACTH the baseline of 4.7 and 4.0 pmol.l-1 was increased by 8.3- and 10.3-fold, respectively. Cortisol concentration rose exponentially from a baseline 17 micrograms.dl-1 and peaked at 2.2-fold 30 min after the run, when the maximal concentration also had been reached after the treadmill test, increasing 1.3-fold from a baseline of 21 micrograms.dl-1. The maximal values for cortisol concentration after both exercises differed from each other, while the maxima of ACTH and beta-endorphin concentrations were similar. The ACTH and beta-endorphin concentration declined more slowly during the recovery after the marathon than after the treadmill. Cortisol concentration was below baseline 24 h later. In comparison with men studied earlier, female marathon runners showed higher baseline concentrations and lesser increases in beta-endorphin and lower baseline concentrations and larger increases in ACTH concentration after both types of exercise. The delayed decrease in concentration of the hormones after the marathon was similar in male and female runners.